Can cultural capital, cognitive ability, and economic capacity help rural older adults bridge the digital divide? Evidence from an empirical study - Cui, Yupeng; He, Youshi; Xu, Xinglong; Zhou, Lulin; Nutakor, Jonathan Aseye (Frontiers in Public Health, 2024)
Background The digital divide is the difference between individuals who use the Internet and those who do not. Under the triple social environment of urban–rural dichotomy, population aging, and the digital era in China, the existence of digital divide among rural older adults has seriously affected their access to health information through the Internet, so it is urgent to bridge the digital divide problem they face. Methods Based on Maslow’s Hierarchy of Needs Theory and Stress Coping Theory, the impact of cultural capital on the digital divide among rural older adults was systematically analyzed using hierarchical regression and Chained Mediation Effect Tests using data from the Chinese Family Panel Studies (CFPS). Results Cultural capital has a significant positive effect on the digital divide among rural older adults (β = 0.178, p < 0.01). Cognitive ability and economic capacity both play independent intermediary effects between cultural capital and digital divide among rural older adults, and the intermediary chain formed by the two plays a chain intermediary effect. The increase in the cultural capital of rural older adults has led to an increase in their cognitive ability and economic capacity, which ultimately has a favorable effect on the bridging of the digital divide. Heterogeneity results suggest that cultural capital is more effective in bridging the digital divide among male rural older adults aged 60–69. Conclusion Cultural capital is able to bridge the digital divide faced by rural older adults and is age and gender heterogeneous. At the same time, improved cognitive ability and economic capacity can also help rural older adults bridge the digital divide. Therefore, it is proposed that we increase the construction of public cultural service infrastructure in rural areas, liaise with community neighborhood committees and village committees to do a good job of publicity, improve training measures for key groups, and maintain the enthusiasm of rural older adults for learning, so as to provide references for the rural older adults in China and developing countries in general to bridge the digital divide.